Azadirachtin‐based insecticide impairs testis morphology and spermatogenesis of the southern armyworm Spodoptera eridania (Lepidoptera: Noctuidae). Issue 5 (16th January 2023) - Scudeler, Elton Luiz; Daquila, Bruno Vinicius; de Carvalho, Shelly Favorito; Conte, Helio; Padovani, Carlos Roberto; dos Santos, Daniela Carvalho
Abstract: Background: In the search for alternative tools for integrated pest management, azadirachtin, a botanical insecticide, has been used with the most promising activity against Spodoptera spp., but the mechanism of cytotoxicity on reproductive organs remains unclear. Spodoptera eridania (Stoll, 1782) is a polyphagous pest with great economic importance that has become an important target to elucidate the action of azadirachtin on the reproductive organs of insect pests, helping to understand the deleterious effects caused by its exposure. This study evaluated the effects of chronic exposure to azadirachtin on the morphology and ultrastructure of S. eridania larval testes as well as larval development. Results: Azadirachtin exposure (6 or 18 mg a.i. L −1 ) caused a progressive increase in cumulative mortality and reduced gain in body mass after 5 days. Testicular structure indicated a reduction in their size with internal morphological changes such as spermatogonia, spermatogonial, spermatocytes and spermatid cysts in degeneration. The occurrence of cell death in germ and somatic cells was evidenced by the TUNEL technique. Electron microscopy revealed changes in cystic cells, such as cytoplasmic membrane rupture and cytoplasmic vacuolization. Chromatin compaction, changes in the rough endoplasmic reticulum and Golgi complex cisternae were observed in germ cells. Apoptotic bodies occurred between germ cell cysts. Conclusion: Azadirachtin damaged the testes of S. eridania larvae, and these changes compromised spermatogenesis and consequently the development of the reproductive potential of this specimen, making azadirachtin a promising botanical insecticide for application in integrated pest management programs. © 2022 Society of Chemical Industry. Abstract : Azadirachtin intake impaired the morphology and size of testes of S. eridania, causing cell damage and cell death in somatic and germ cells, and affecting the spermatogenesis process.